2021
DOI: 10.3389/fpsyg.2021.761378
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian and Maximum-Likelihood Modeling and Higher-Level Scores of Interpersonal Problems With Circumplex Structure

Abstract: Difficulties in interpersonal behavior are often measured by the circumplex-based Inventory of Interpersonal Problems. Its eight scales can be represented by a three-factor structure with two circumplex factors, Dominance and Love, and a general problem factor, Distress. Bayesian confirmatory factor analysis is well-suited to evaluate the higher-level structure of interpersonal problems because circumplex loading priors allow for data-driven adjustments and a more flexible investigation of the ideal circumplex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…And someone who is "conflict averse" (HI7) is likely to be "indulgent" (JK4) as well. This finding is in line with previous research on the interpersonal circumplex, where the two subscales HI and JK have been found to be closer than the expected 45° as well (Alden et al, 1990;Jacobs & Scholl, 2005;Weide et al, 2021). To better differentiate between the two subscales, it could be beneficial to generate new items that better capture the domain "JK/Unassuming-ingenuous" and disentangle it from its neighboring domain.…”
Section: Interpretation Of Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…And someone who is "conflict averse" (HI7) is likely to be "indulgent" (JK4) as well. This finding is in line with previous research on the interpersonal circumplex, where the two subscales HI and JK have been found to be closer than the expected 45° as well (Alden et al, 1990;Jacobs & Scholl, 2005;Weide et al, 2021). To better differentiate between the two subscales, it could be beneficial to generate new items that better capture the domain "JK/Unassuming-ingenuous" and disentangle it from its neighboring domain.…”
Section: Interpretation Of Resultssupporting
confidence: 87%
“…We used data from an online-questionnaire study, from which a different part of the data has been published within another project (Weide et al, 2021). The study conformed with the Declaration of Helsinki and was approved by the ethics board of the University of Bonn.…”
Section: Methods (Sample Variables)mentioning
confidence: 99%
“…However, there are cautionary notes on the use of default settings for convergence (Zitzmann & Hecht, 2019) or on the use of default prior distributions (Smid & Winter, 2020). Nevertheless, Bayesian factor analysis (BFA) is meanwhile regularly used (e.g., Bonafede et al, 2021; Wang et al, 2021; Weide et al, 2021). It follows from the regular use of BFA that plausible values as factor score estimates computed from BFA (Asparouhov & Muthén, 2010a, 2010b) may also be used regularly.…”
mentioning
confidence: 99%
“…Advantages of BSEM are that it can be performed with relatively small samples (Bonafede, Chiorri, Azzolina, 2021) and that priors for the variability of loadings can be specified. BSEM thereby allows to overcome problems of specifying fixed zero loadings in the independent clusters model (Beauducel & Hilger, 2020) and it also allows for the specification of complex loading patterns as, for example, circumplex models (Weide, Scheuble, & Beauducel, 2021).…”
Section: The Validity Of Mean Plausible Valuesmentioning
confidence: 99%